2021
DOI: 10.3389/fpsyg.2021.631062
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity and Employees’ Extra-Role Behavior: Moderated Mediation Model of Negative Emotion and Workplace Friendship

Abstract: Based on the affective events theory, this paper discusses the influence of job insecurity on employees’ extra-role behavior. The mediating effect of negative emotion and the moderating effect of workplace friendship are also tested. The results of an empirical analysis, based on the data of 327 employees, show that job insecurity has a significant negative impact on employees’ extra-role behavior. Negative emotion plays a mediating role in the relationship between job insecurity and extra-role behavior. Workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 51 publications
6
33
0
Order By: Relevance
“…Although Teng et al (2019) found that job insecurity can promotes employees’ innovative behavior. This finding is consistent with the conclusions of most of those previous researches on the impact of job insecurity on positive behaviors, that is, job insecurity has a significant negative impact on employees’ positive behaviors, such as voice behavior ( Yin and Chung, 2019 ) and extra-role behavior ( Yu et al, 2021 ). It may be related to the increase of psychological stress and the decrease of organizational commitment of employees ( Chirumbolo et al, 2017 ) caused by job insecurity.…”
Section: Discussionsupporting
confidence: 92%
“…Although Teng et al (2019) found that job insecurity can promotes employees’ innovative behavior. This finding is consistent with the conclusions of most of those previous researches on the impact of job insecurity on positive behaviors, that is, job insecurity has a significant negative impact on employees’ positive behaviors, such as voice behavior ( Yin and Chung, 2019 ) and extra-role behavior ( Yu et al, 2021 ). It may be related to the increase of psychological stress and the decrease of organizational commitment of employees ( Chirumbolo et al, 2017 ) caused by job insecurity.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated significant moderation effects of workplace friendship on the relationship. The results of this study are somewhat similar to the study conducted by Yu et al (2021). They also used workplace friendship as a moderator.…”
Section: Discussionsupporting
confidence: 85%
“…However, until now, even when this relationship could be assumed, it is ideally a derived one without any sufficient empiricism. Besides, the mediation tests alluded to in the present study, are not mentioned anywhere in the study by Yu et al (2021). Therefore, it was necessary then to hypothesize that: H 5 .…”
Section: Employee Optimism Status Competitiveness Interpersonal Adaptability and Employee Altruismmentioning
confidence: 75%
“…In a related argument by Yu et al (2021), there is another point of view against which to derive a possible linkage amongst these variables, but definitely with marked weaknesses. These scholars argue that workplace friendship results in the achievement of individuals' emotional needs in the organization, knowledge sharing, mutual help among workmates, harmonious working atmosphere characterized by mutual trust and love and increased resource investment in extrarole behavior.…”
Section: Employee Optimism Status Competitiveness Interpersonal Adaptability and Employee Altruismmentioning
confidence: 99%